Characterization of faba bean and chickpea viruses causing yellowing and stunting symptoms in Tunisia - Mghandef, Samia; Kumari, Safaa; Najar, Asma (The Arab Society for Plant Protection, 2022)
In Tunisia, faba bean (Vicia faba) and chickpea (Cicer arietinum) are considered as strategic crops because of their economic and social relevance and significant direct contribution towards the national food balance. However, production levels of these crops remain quite low which is often attributed to abiotic and biotic stresses that are prevailing in the major growing areas. Viruses causing yellowing and stunting symptoms represent one of the major constraints that reduce the genetic potential of most cultivated species and varieties. To characterize these viruses in Tunisia, field surveys were conducted in five main regions (Béja, Bizerte, Cap-Bon, Jendouba and Kef) during 2018 and 2019 growing seasons. A total of 389 faba bean and 182 chickpea samples with yellowing and stunting symptoms were collected and tested by tissue blot immunoassay (TBIA) using specific monoclonal antibodies (MAbs). Laboratory results showed that Chickpea chlorotic stunt virus (CpCSV) was the most common virus detected in 47.6% of faba bean and 18.7% of chickpea tested samples, followed by Beet western yellows virus (BWYV) (28% in faba bean and 4.4% in chickpea). Whereas, only 8.8% of faba bean samples were infected with Faba bean necrotic yellows virus (FBNYV), and Bean leafroll virus (BLRV) in faba bean (6.7%) and chickpea (9%) samples. To confirm the presence of yellowing viruses in Tunisia, total RNA was extracted from 5 faba bean and 27 chickpea samples that showed positive reaction to BLRV MAb (8 samples: 2 faba bean, 6 chickpea), BWYV MAb (7 samples: 2 faba bean, 5 chickpea) and CpCSV MAb (17 samples: 1 faba bean, 16 chickpea). Reverse transcription-polymerase chain reaction (RT-PCR) was performed using specific luteovirus primer pairs. RT-PCR amplicons of the expected size of each primer were obtained from 32 samples and were sequenced in both directions. Molecular results showed that BWYV and CpCSV (both belong to genus Polerovirus, family Solemoviridae) and BLRV (belong to genus Luteovirus, family Tombusviridae) were identified in Tunisia, and the coat protein nucleotide sequence analysis of the Tunisian isolates showed 99% homology to Moroccan isolate (CpCSV), 97% homology to the French isolate (BWYV), and 98% homology to Argentina isolate (BLRV).